Faktor Risiko Kejadian Stroke di Usia Produktif - Rizky Agung Purnomo; Ade Yonata; Intanri Kurniati (CV. Jasa Sukses Abadi, 2022)
Stroke is a disorder due to focal or global brain function disorders that occur triggered by cerebrovascular disorders. Stroke is characterized by paralysis of the face or limbs, difficulty speaking, decreased consciousness, and visual disturbances. Stroke is the number 2 cause of death in the world, which is about 6 million deaths every year. Recently, stroke does not only occur in the elderly population, but also in the productive age. This article is a literature compiled to analyze the risk factors associated with the incidence of stroke in productive age. The references used are articles published between 2016-2022. There are 4 main risk factors for stroke in productive age, namely hypertension, diabetes mellitus, dyslipidemia, and lifestyle. Each factor plays a role in increasing the risk of stroke with its own mechanism. There is no difference between stroke risk factors in the productive age and the general population.